The relationship between porosity and specific surface in human cortical bone is subject specific - Lerebours, C.; Thomas, C.D.L.; Clement, J.G.; Buenzli, P.R.; Pivonka, P. (Bone (New York, N.Y.), 2015)
A characteristic relationship for bone between bone volume fraction (BV/TV) and specific surface (BS/TV) has previously been proposed based on 2D histological measurements. This relationship has been suggested to be bone intrinsic, i.e., to not depend on bone type, bone site and health state. In these studies, only limited data comes from cortical bone. The aim of this paper was to investigate the relationship between BV/TV and BS/TV in human cortical bone using high-resolution micro-CT imaging and the correlations with subject-specific biometric data such as height, weight, age and sex. Images from femoral cortical bone samples of the Melbourne Femur Collection were obtained using synchrotron radiation micro-CT (SPring8, Japan). Sixteen bone samples from thirteen individuals were analysed in order to find bone volume fraction values ranging from 0.20 to 1. Finally, morphological models of the tissue microstructure were developed to help explain the relationship between BV/TV and BS/TV. Our experimental findings indicate that the BV/TV vs BS/TV relationship is subject specific rather than intrinsic. Sex and pore density were statistically correlated with the individual curves. However no correlation was found with body height, weight or age. Experimental cortical data points deviate from interpolating curves previously proposed in the literature. However, these curves are largely based on data points from trabecular bone samples. This finding challenges the universality of the curve: highly porous cortical bone is significantly different to trabecular bone of the same porosity. Finally, our morphological models suggest that changes in BV/TV within the same sample can be explained by an increase in pore area rather than in pore density. This is consistent with the proposed mechanisms of age-related endocortical bone loss. In addition, these morphological models highlight that the relationship between BV/TV and BS/TV is not linear at high BV/TV as suggested in the literature but is closer to a square root function. •Analysing cortical bone sections using high‐resolution imaging (synchrotron radiation, SPring8)•Establishing a relation between bone volume fraction and specific surface and identifying the patient and site‐specificity of this relation•Development of computational models of Haversian pores simulating the increase of cortical porosity and merging of pores•Imaging data and computational modelling indicate that increases in cortical porosity are mainly driven by merging of Haversian pores.•Comparison of our experimental data with previously reported data obtained by Bruce Martin and co-workers